Pengaruh Aplikasi Wordwall terhadap Perkembangan Bahasa dan Sosial Emosional Anak Usia Dini - Suhartinah Suhartinah; Erna Budiarti (Jurnal Studi Guru dan Pembelajaran, 2024)
During critical periods, a child's cognitive, social, emotional, and language development is essential for their growth and development. The development of these skills involves cognitive, emotional and social skills, which are influenced by various factors such as IQ, EQ, SQ and RQ. The utilization of technology in education is an important approach. One of the technologies that can be used is the wordwall application. The utilization of this technology was chosen because when students listen to stories told by the teacher in class through picture storybooks, children do not focus on listening so that the meaning or content in the contents of the storybook that is read is not understood by students. After five to ten minutes, the children are already running around looking for more interesting things. The purpose of this study was to determine the effect of wordwall application on language, social and emotional development of early childhood. The research method used is the experimental method, with a pre-assessment and post-assessment research design, while the type of research is quantitative whose research results are: 1) Wordwall application has an effect on early childhood language development with the results of research p value of 0.016 <0.05, 2) Wordwall application affects early childhood social development with the results of research p value of 0.017 <0.05, 3) Wordwall application affects early childhood emotional development with the results of research p value of 0.007 <0.05.